A Joint Evaluation With Lessons for the Sustainable Development Goals Era: The Joint GEF-UNDP Evaluation of the Small Grants Programme. (June 2020) - Carugi, Carlo; Bryant, Heather
The integrated nature of the Sustainable Development Goals (SDGs) calls for greater synergy, harmonization, and complementarity in development work. This is to be reflected in evaluation. Despite a long and diversified history spanning over almost three decades, joint evaluations have fallen out of fashion. Evaluators tend to shy away from joint evaluations because of timeliness, institutional and organizational differences, and personal preferences. As the SDGs call for more joint evaluations, we need to get them right. This article supports the appeal for more joint evaluations in the SDGs era by learning from the existing long and diversified experience. This article shares lessons from a joint evaluation that is relevant in the context of the SDGs for the United Nations Evaluation Group, the Evaluation Cooperation Group, and the wider international evaluation community.